Climate Change and Rural Livelihoods in the Lawra District of Ghana. A Qualitative Based Study - Abdulai, Abdul-Rahim; Ziemah, Marshal K.; Akaabre, Paul Boniface (European Scientific Journal, ESJ, 2017)
Climate change is a growing threat to the world's poorest and most vulnerable living in rural areas. The impacts of climate change challenge efforts to reducing poverty and hence, will require new approaches to focus development programming on the changing realities of the world. Understanding how the impacts of climate change affect the people, and their knowledge and experience in coping with it will assist in identifying appropriate strategies for adaptation to it. This paper thus examined the impacts of climate change on livelihoods of rural communities in the Upper West region of Ghana and the challenges posed to efforts at reducing poverty in the area. Discussions on vulnerability to climate variability and adaptation issues in this paper focused on evidence observed by 10 communities in the Lawra District. Adopting a qualitative approach, ten focused group discussions were organized to gather data. Specific issues discussed surrounded evidence of climate change in the communities, its impacts, underlying causes of vulnerability to climate and coping strategies employed by community members. Based on the discussions, the paper recommends the need to develop and intensify effective institutional mechanisms to facilitate community adaptation measures, awareness raising (creation) on anti-environments practices in communities, institution of bye and customary laws to regulate human anti-environmental activities, and the implementation of adaptation projects to aid communities cope with the major impacts of climate change in the district and world at large.